Diversity of Ethnomedicines of Valayan Tribes of Kidari Hills in the Eastern Ghats, Tamil Nadu, South India - Santhanapandi, P.; Gnanasekaran, T.; Nagavalli, K.; Geetha, S.; A.; Chittibabu, C.V. (Indian Forester, 2024)
The diversity of extant ethnomedicines of the Eastern Ghats were inventoried during the months of June to August 2018 in Kidari hills. The species diversity include 79 medicinal plants of the Valayan tribes in the study area, which were tabulated with vernacular and botanical names, IUCN Criteria, family name, part(s) used, drug type, and mode of drug administration for the human disease(s). The family diversity revealed that Fabaceae (with 11 plant species) is apex in the list among the total 38 plant families; further, 69 belong to 31 families of dicotyledons (82%) and 10 plants belong to 7 families of monocotyledons (18%). The analysis of IUCN Red List showed that Chloroxylon swietenia DC. and Aegle marmelos (L.) Correa. (Rutaceae) are enlisted as Vulnerable and Near Threatened respectively and gain greater significance. The life forms of ethnomedicinal plants predominantly used by the Valayan tribes were herbs (51%) followed by plant parts used leaves (31%) were used; Based on their drug type, it is found that the juice form of drug (62%) were preferred for ethnomedicinal preparation. Further, the single drug (70%) topped the list and their overall 24% depletion underscore the urgency to conserve them.